Design of a Scale Fluidized Bed Dryer for Laboratory (LACCEI, 2024)
The drying process is the most important stage required for conserving grains, cereals, and vegetables, thus avoiding the generation of fungi, allowing the product to be preserved for longer [1]. Therefore, there are several projects where tests are involved in the laboratories of Higher Educational Institutions to help with technology and food conservation issues for companies and agricultural communities. The drying technologies are assessed by determining each food's time, temperature, humidity, and drying speed. Through a valuation matrix, a type of dryer has been selected, which will be presented in this work, whose objective is to design and build a fluidized bed dryer for drying 2 kg of a wet sample, applying the reuse of materials (Circular economy) to reduce the cost of construction. We start with the applied methodological scheme for the design, engineering analysis of each part of the equipment, construction, and functional test of fluidized bed equipment at laboratory scale. As a result, the equipment works between temperatures of 50 ° C to 70 ° C, adjustable speeds between 4 to 11 m / s, drying time 8 hours, consumption of 1.7 kW / h, whit construction savings of 40%. Finally, we can conclude that it is possible to build drying technology on a laboratory scale where must consider the main source of energy, available area, noise and vibrations within the design in addition, a laminar flow must be supplied that allows a homogeneous drying of the produc